DEVELOPING WORK ORDER MANAGEMENT SYSTEM WITH CIRCULAR ECONOMY APPROACH USING ASAP METHOD - Tomi, Tomi; Mulyono, Nur Budi (LPPM STIE Muhammadiah Bandung, 2025)
CV PG STTT is a garment manufacturing company that specializes in producing chemical laboratory coats and technical PDL (Personal Duty Line) shirts. The company operates on a make-to-order system. However, its production processes remain entirely manual, resulting in challenges related to production monitoring, tracking, and recording. Furthermore, the company still adheres to a linear economy model, where production waste is discarded without being repurposed. To address these issues, the implementation of an extended work order management system using a circular economy approach offers a viable solution. This approach not only minimizes production waste but also enhances the monitoring of production processes. The extended work order management system is developed using the Accelerated SAP (ASAP) methodology. The research follows several stages, including observation, interviews, analysis, and the proposal of a system design through configuration and adjustment of manufacturing modules, followed by testing the manufacturing modules. The outcome of this study is an ERP system on Odoo with customized module to align with the company's business processes and proposed workflows. This system simplifies production processes at CV PG STTT while promoting sustainability and supporting the transition to a circular economy.